Identificação de genes candidatos ao desenvolvimento de Leiomiomas Uterinos - Rosa, Luciana Albina Reis [UNESP] (Universidade Estadual Paulista (Unesp), 2008)
Uterine leiomyomas (UL) are benign smooth muscle tumors from myometrium, representing the major indication for hysterectomies and a significant public health problem. Several genetics alterations have been associated with its development and pathogenesis. Although the initial factors that lead to the development of uterine leiomyomas are unclear, there are several evidences showing that ovarian steroids, estrogen and progesterone, are associated with these tumors.Recent reports, however, show others genes related with distinct signalization pathways besides sex hormones, which may be or not activated by these hormones, are associated with uterine leiomyomas development. In this study, the AHR, ESR1, ESR2, PGR and WNT7A gene transcripts expression was evaluated using quantitative real time RT-PCR in 58 UL samples compared to five normal myometrium tissues to explore the hormonal molecular basis of these tumors and associate these expression pattern with clinical and pathological features. The present study showed AHR, ESR1, ESR2, PGR and WNT7A down expression in 60%, 43%, 52%, 60% e 40% of the tumors, respectively, and a significant AHR loss of expression compared with the controls samples (P=0.0130). The comparison between the genes expression values revealed a positive correlation between the AHR and ESR1 transcripts (P<0.0001; r=0.6911) and between the genes ESR1 and WNT7A (P<0.0001; r=0.5655). The expression pattern was compared with clinical and pathological features. The WNT7A gene presented a differential expression pattern between the proliferative and secretory phase of menstrual cycle (P=0.0373) and the AHR and ESR1 genes were differentially expressed between women in reproductive and menopause years (P=0.0267; P=0.0415, respectively). The ESR1 and WNT7A down regulation was statistically ...(Complete abstract click electronic access below)

Leiomiomas uterinos (LU) são neoplasias benignas da musculatura lisa do miométrio, constituindo a principal causa de indicação para histerectomia e um importante problema de saúde pública. Uma variedade de alterações genéticas tem sido associada ao desenvolvimento e à patogênese desta neoplasia. Embora os fatores iniciais que levam ao desenvolvimento destes tumores serem desconhecidos, há muitas evidências mostrando que os esteróides ovarianos, estrógeno e progesterona, são importantes fatores para o crescimento tumoral. Estudos recentes, entretanto, revelam que outros produtos gênicos relacionados com vias de sinalização distintas além dos hormônios sexuais, podendo ou não ser ativadas por estes hormônios, estão associados com o desenvolvimento dos LU. Neste estudo foi avaliada a expressão dos transcritos dos genes AHR, ESR1, ESR2, PGR e WNT7A por RT-PCR quantitativa em tempo real em 58 amostras de LU comparados com cinco amostras de miométrio normal para explorar a base molecular hormonal desses tumores e associar estes achados com dados clínico-patológicos das pacientes. Os dados do presente estudo mostraram diminuição de expressão para os genes, AHR, ESR1, ESR2, PGR e WNT7A em 60%, 43%, 52%, 60% e 40%, respectivamente. Foi observada uma significativa diminuição da expressão do gene AHR comparado às amostras controles (P=0,0130). A quantificação relativa dos genes avaliados mostrou uma correlação positiva entre os transcritos AHR e ESR1 (P<0,0001; r=0,6911) e entre os genes ESR1 e WNT7A (P<0,0001; r=0,5655). O gene WNT7A mostrou-se diferencialmente expresso nas fases proliferativa e secretória do ciclo menstrual (P=0,0373) e os genes AHR e ESR1 entre as mulheres cíclicas e as menopá...(Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Utero - Doenças - Aspectos genéticos; Leiomioma uterino - Aspectos genéticos; Expressão gênica